Electrolyte Additive-Assembled Interconnecting Molecules–Zinc Anode Interface for Zinc-Ion Hybrid Supercapacitors - Li, Yang; Li, Xu; Peng, Xinya; Yang, Xinyu; Kang, Feiyu; Dong, Liubing (Nano-Micro Letters, 2025)
Zinc-ion hybrid supercapacitors (ZHSs) are promising energy storage systems integrating high energy density and high-power density, whereas they are plagued by the poor electrochemical stability and inferior kinetics of zinc anodes. Herein, we report an electrolyte additive-assembled interconnecting molecules–zinc anode interface, realizing highly stable and fast-kinetics zinc anodes for ZHSs. The sulfobutyl groups-grafted β-cyclodextrin (SC) supramolecules as a trace additive in ZnSO4 electrolytes not only adsorb on zinc anodes but also self-assemble into an interconnecting molecule interface benefiting from the mutual attraction between the electron-rich sulfobutyl group and the electron-poor cavity of the adjacent SC supramolecule. The interconnecting molecules–zinc anode interface provides abundant anion-trapping cavities and zincophilic groups to enhance Zn2+ transference number and homogenize Zn2+ deposition sites, and meanwhile, it accelerates the desolvation of hydrated Zn2+ to improve zinc deposition kinetics and inhibit active water molecules from inducing parasitic reactions at the zinc deposition interface, making zinc anodes present superior reversibility with 99.7% Coulombic efficiency, 30 times increase in operation lifetime and an outstanding cumulative capacity at large current densities. ZHSs with 20,000-cycle life and optimized rate capability are thereby achieved. This work provides an inspiring strategy for designing zinc anode interfaces to promote the development of ZHSs. Highlights: 1 An important topic about zinc-ion hybrid supercapacitors is proposed, i.e., how to achieve not only ultrastable but also fast-kinetics zinc anodes to match capacitive cathodes featuring ultralong cycle life and fast charge storage ability. 2 An electrolyte additive-assembled interconnecting molecules–zinc anode interface is proposed, and its regulation mechanisms on zinc plating/stripping behaviors are revealed. 3 A scalable strategy is reported for achieving highly stable and fast-rate zinc anodes toward zinc-based electrochemical energy storage systems.